Factors associated with delays in revascularization in patients with chronic limb-threatening ischaemia: population-based cohort study. Issue 8 (11th April 2021) - Birmpili, P; Johal, A; Li, Q; Waton, S; Chetter, I; Boyle, J R; Cromwell, D
Abstract: Background: Prompt revascularization in patients with chronic limb-threatening ischaemia (CLTI) is important, and recent guidance has suggested that patients should undergo revascularization within 5 days of an emergency admission to hospital. The aim of this cohort study was to identify factors associated with the ability of UK vascular services to meet this standard of care. Methods: Data on all patients admitted non-electively with CLTI who underwent open or endovascular revascularization between 2016 and 2019 were extracted from the National Vascular Registry. The primary outcome was interval between admission and procedure, analysed as a binary variable (5 days or less, over 5 days). Multivariable Poisson regression was used to examine the relationship between time to revascularization and patient and admission characteristics. Results: The study analysed information on 11 398 patients (5973 open, 5425 endovascular), 50.6 per of whom underwent revascularization within 5 days. The median interval between admission and intervention was 5 (i.q.r. 2–9) days. Patient factors associated with increased risk of delayed revascularization were older age, greater burden of co-morbidity, non-smoking status, presentation with infection and tissue loss, and a Fontaine score of IV. Patients admitted later in the week were less likely undergo revascularization within 5 days than those admitted on Sundays and Mondays ( P < 0.001). Delays were slightly worse among patients having open compared with endovascular procedures ( P = 0.005) and in hospitals with lower procedure volumes ( P < 0.001). Conclusion: Several factors were associated with delays in time to revascularization for patients with CLTI in the UK, most notably the weekday of admission, which reflects how services are organized. The results support arguments for vascular units providing revascularization to have the resources for a 7-day service. Lay summary: Chronic limb-threatening ischaemia (CLTI) is a severe form of peripheral artery disease that reduces blood flow to the legs and can lead to amputation. Between 2016 and 2019, only 50.6 per cent of patients admitted to UK vascular units urgently with CLTI underwent revascularization within 5 days from admission. Several factors were associated with delays in time to revascularization, most notably the weekday of admission, which reflects how services are organized. The results support arguments for vascular units providing revascularization to have resources for a 7-day service. Abstract : Between 2016 and 2019, only half of patients admitted non-electively to UK vascular units with chronic limb-threatening ischaemia underwent revascularization within 5 days from admission. Several factors were associated with delays in time to revascularization, most notably the weekday of admission, which reflects how services are organized. The results support arguments for vascular units providing revascularization to have the resources for a 7-day service.